Public sector innovation and the demand-side innovation policies. Summary: Avaliku sektori innovatsioonid ja nõudluspoolsed innovatsioonipoliitikad - Roolaht, Tõnu (Estonian Discussions on Economic Policy, 2013)
The public sector innovations are important additions to private and social efforts towards development oriented changes in society. These innovations aim at improving the efficiency and societal value of public services. In order to do so, the new organisational arrangements as well as public-private partnerships are often called for. In these situations, the novel service configurations are designed by public policy makers, but the actual service provision might be delegated to private companies or to non-governmental organisations (NGOs). This kind of combined execution creates strong connection between public sector innovations and demandside innovation policies. The purpose of this study is to offer the possible ways to combine public sector innovations with demand-side innovation policies in Estonia. This would allow building strong ties between innovative advances in private and public sectors, thus enhancing the change towards knowledge-based society.